DNA replication - Patel, Smita (Henry Stewart Talks, 2007)
DNA structure, Semiconservative DNA replication, Mechanism of DNA replication, DNA polymerase structure and function, Metal ions in DNA synthesis, Rates of correct and incorrect nucleotide addition, Fidelity of DNA synthesis, Helicase in DNA replication, DNA primase protein, DNA replicase
Reviewed at 2022/04/27